Problems of Implementation of Alimony Rights and Obligations of Parents and Children - Джалилов Азамат Амриллоевич (Scientific Trends, 2026)
This article analyzes topical problems of implementing alimony rights and obligations of parents and children. The article thoroughly examines the object, subjects and content of alimony legal relations. Issues of ensuring a child's adequate standard of living, the emergence and implementation of alimony obligations are covered based on legislative norms. The legal status of such subjects as the alimony payer, alimony recipient and child is analyzed. The article also examines the right of a minor child to dispose of alimony funds, civil legal capacity and mechanisms for protecting the child's interests. The author presents practical proposals for improving existing legislation.
Keywords: Alimony, parental obligations, child rights, alimony legal relations, minor child, alimony payer, alimony recipient, child's interests, civil legal capacity, Family Code.